The value of performing cerebrovascular CT angiography in major trauma patients: a 5-year retrospective review. Issue 3 (March 2023) - Saqib, R.; Madhavan, A.; Thornber, E.; Siripurapu, R.; Choi, C.; Holsgrove, D.; Bailey, K.; Thomas, M.; Hilditch, C.A.
Abstract : AIM: To assess whether routine cerebrovascular imaging is required in all major trauma (MT) patients. MATERIALS AND METHODS: All MT patients with cerebrovascular imaging between January 2015 and December 2020 were included in the study. Data were collated regarding the type of indication for computed tomography (CT) angiography imaging, time interval from the initial trauma, relevant trauma diagnoses on initial trauma imaging, and CT angiography. Findings, such as aneurysms, vascular malformations, luminal thrombus, venous sinus thrombosis, or vascular injury, were collated. Subsequent treatment with anti-coagulants/anti-platelets or surgical/radiological intervention was noted. Follow-up imaging was assessed for residual injury or complications. RESULTS: Two hundred and fifty of the 6, 251 MT patients underwent dedicated cerebrovascular imaging and were included in the study. Of these 41 (16.4%) had cervical artery or venous sinus injury. Further positive vascular findings were identified in 25/250 patients who presented with an incidental stroke or a vascular abnormality and were mislabelled as MT patients at presentation. One patient with a carotid injury subsequently died following a large infarction. Another patient with vertebral artery injury suffered a non-lethal stroke. No patients underwent surgery or intervention. CONCLUSION: The present study showed that the overall incidence of detected blunt cerebrovascular injuries was very low (0.6%) and even lower for symptomatic vascular injury (0.03%). Routine cerebrovascular imaging is not recommended in all MT trauma patients, but instead, a continued case-by-case basis should be considered. Highlights: The overall incidence of detected blunt cerebrovascular injury was very low (0.6%). Incidence of symptomatic cerebrovascular injury was even lower at 0.03%. We do not recommend routine cerebrovascular imaging in all MT trauma patients. A continued case-by-case consideration for cerebrovascular imaging is suggested.